2018
DOI: 10.1126/sciadv.aar3938
|View full text |Cite
|
Sign up to set email alerts
|

ETV7 is an essential component of a rapamycin-insensitive mTOR complex in cancer

Abstract: A novel mTOR complex assembled by the ETS transcription factor ETV7 contributes to rapamycin resistance in cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
127
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(127 citation statements)
references
References 62 publications
(101 reference statements)
0
127
0
Order By: Relevance
“…mTOR is atypical serine/threonine protein kinase from the phosphoinositide 3-kinase (PI3K)-related kinase family, which maintains the balance between anabolic and catabolic processes in response to a variety of physiological and pathological conditions [66]. mTOR pathway regulates myriad biological processes such as protein synthesis, proliferation, autophagy, metabolism, cell survival, and others through distinct protein complexes including mTOR complex 1 (mTORC1), mTOR complex 2 (mTORC2) and mTOR complex 3 (mTORC3) [66,67]. The most intensively studied of all mTOR complexes is undoubtedly mTORC1.…”
Section: Discussionmentioning
confidence: 99%
“…mTOR is atypical serine/threonine protein kinase from the phosphoinositide 3-kinase (PI3K)-related kinase family, which maintains the balance between anabolic and catabolic processes in response to a variety of physiological and pathological conditions [66]. mTOR pathway regulates myriad biological processes such as protein synthesis, proliferation, autophagy, metabolism, cell survival, and others through distinct protein complexes including mTOR complex 1 (mTORC1), mTOR complex 2 (mTORC2) and mTOR complex 3 (mTORC3) [66,67]. The most intensively studied of all mTOR complexes is undoubtedly mTORC1.…”
Section: Discussionmentioning
confidence: 99%
“…9 A serine/threonine kinase, mTOR exists as a component member of three separate complexes, mTOR complex 1 (mTORC1), mTOR complex 2 (mTORC2), 9 and the recently identified mTOR complex 3 (mTORC3). 10 Acute rapamycin treatment has been shown to inhibit mTORC1 only, with mTORC2 11 and mTORC3 insensitive to its effects. 10 Because of its integral role in various signaling pathways, 9 mTOR dysfunction has been linked to a number of disease states, including ocular disorders.…”
mentioning
confidence: 99%
“…10 Acute rapamycin treatment has been shown to inhibit mTORC1 only, with mTORC2 11 and mTORC3 insensitive to its effects. 10 Because of its integral role in various signaling pathways, 9 mTOR dysfunction has been linked to a number of disease states, including ocular disorders. 12 Previous studies have demonstrated the ability of rapamycin to reduce retinal neovascularization in vitro 13 and in vivo 14 by inhibiting mTORC1, which acts through hypoxia inducible factor 1α (HIF-1α) to downregulate VEGF.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its translocation function, the overexpression of ETV7 has been associated with tumorigenic transformation and anti-apoptosis by blocking Mys-induced apoptosis pathway (26)(27)(28). Furthermore, there are growing experimental evidences showing that ETV7 also plays a significant role in mTOR signaling pathway by assembling mTOR3 complex, which can stimulate cell proliferation and is not sensitive to rapamycin, a common anti-tumor agent, unlike mTOR1/2 (29). So the depletion of ETV7 may cause the inactivation of mTOR3, thus leading to tumor cell death after treatment.…”
Section: Precise Stratification Of Tcga-lihc Samples Based On Metabolmentioning
confidence: 99%